2009
DOI: 10.1007/s10509-009-0237-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between phantom field and modified Chaplygin gas

Abstract: In this letter, we have considered a flat FRW universe. Instead of considering only one candidate for dark energy, we have considered interaction between phantom field and modified Chaplygin gas. It has been shown that the potential of the phantom field increases from a lower value with evolution of the Universe. It has been observed that, the field has an increasing tendency and potential has also an increasing tendency with passage of cosmic time. In the evolution of the universe the crossing of $w=-1$ has b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…By combining Eqs. (14) and (15) and using the large-scale-factor approximation, we have the potential as…”
Section: Case 2: Late Universementioning
confidence: 99%
See 1 more Smart Citation
“…By combining Eqs. (14) and (15) and using the large-scale-factor approximation, we have the potential as…”
Section: Case 2: Late Universementioning
confidence: 99%
“…Two of the most common such attempts come either in the form of modifications to the theory of gravity or the introduction of new matter or scalar field contributions to the action of General Relativity (GR). In the latter case, one suggestion is that the change in the behavior of the missing energy density might be regulated by the change in the equation of state of the background fluid instead of the form of the potential [14,15]. The Chaplygin Gas (CG) model in cosmology is one of the most profound candidates for this suggestion.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that we can put for energy densities (14) and (15) ω 1 = −1 and ω 2 = 1 and identify ρ 1 (t) = V (φ), ρ 2 (t) = ǫφ 2 /2, but in this case we can not write the scale factor, for C 1 = 0 and C 2 = 0, in analytical form. For the case C 1 = 0, C 2 = 0 the solutions are included in (22) and (23).…”
Section: A Exponential Potential In Flat Frw Cosmologiesmentioning
confidence: 99%
“…In recent years, some researchers made some studies on the thermal equation of state to MCG and found that it could cool down in some constraints of parameters [6]. To know more interesting results related to MCG, the readers are referred to [7][8][9][10][11][12]. If = 0, the system (1) becomes the homogeneous modified Chaplygin gas equations.…”
Section: Introductionmentioning
confidence: 99%